The Effectiveness of Laser Peripheral Iridotomy in Adolescent Eyes with Ocular Hypertension and Concave Configuration of the Peripheral Iris - Alina Bakunowicz-Łazarczyk; Beata Urban; Małgorzata Krętowska (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of laser peripheral iridotomy (LPI) in preventing deterioration in eyes with ocular hypertension (OHT) and concave configuration of the iris. Materials and Methods. This was a retrospective study, which was carried out within a period of 3–5 years. Twenty-four patients with OHT and concave irises were treated with LPI and followed up periodically. IOP, central corneal thickness (CCT), anterior chamber depth (ACD), scleral spur angle (SSA), global neuroretinal rim (NRR) thickness, and global retinal nerve fiber layer (RNFL) were examined before and after LPI. Results. The average age of the 24 patients was 14.21 ± 1.41 (13–17.5) years on admission. The initial IOP of the 48 eyes was 23.21 ± 1.56 mmHg in RE and 22.96 ± 2.1 mmHg in LE before LPI. All 48 eyes had concave irises in both eyes. All eyes treated with LPI have shown iris flattening, which has persisted during follow-up (mean 1.54 ± 0.9 years). At the last follow-up visit, the average IOP was 17.58 ± 2.63 (14–21) mmHg in RE and 17.58 ± 2.86 (14–21) mmHg in LE, which was statistically lower than that of the baseline (p<0.001). There were significant changes in SSA in both eyes and global RNFL in RE after LPI. Conclusions. In the current study, LPI resulted in an IOP-lowering effect and iris flattening in adolescent eyes with a concave configuration of the peripheral iris.